Identification of maloyl glucans from Euphorbia tirucalli by ESI-(−)-FT-ICR MS analyses. (June 2015) - Kuster, R.M.; Caxito, M.L.C.; Sabino, K.C.C.; da Costa, H.B.; Tose, L.V.; Romão, W.; Vaz, B.G.; Silva, A.G.
Graphical abstract: Highlights: Euphorbia tirucalli was analyzed for malic acid derivatives. Five compounds were identified as maloyl glucans by ESI-(−)-FT-ICR MS. Mechanism of mass fragmentation was proposed for each molecule. Abstract: Euphorbia tirucalli aerial parts are popularly used in Brazil for cancer treatment. The elution of the aqueous extract of the plant on silica gel C-18 cartridge furnished a water-soluble fraction, which was analyzed directly into the electrospray ionization (ESI) source combined with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and characterized as a mixture of malic acid glycosides 1 –5 . The compounds were detected in their deprotonated form [M−H] −, where their exact mass (mass error lower than 1 ppm), molecular formula (C n H h O o ), double bond equivalent (DBE) and connectivity were determined from ESI-(−)-MS and ESI-(−)-MS/MS experiments. The presence of malic acid and glucose, as part of the structures, could originate from crassulacean acid metabolism (CAM) of the plant.